Penerapan Manajemen Perubahan dan Inovasi pada Suatu Organisasi (Studi Kasus: Harian Pagi Koran Riau) - Fahmi Rizky; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Application of Change Management and Innovation. This research intends to analyze and study the extent to which the application of change management and innovation was carried out in the Riau Daily Morning Koran to attract the attention of the people. This study uses a qualitative method with a single case study approach. This method is used in order to be able to describe the case in a comprehensive, broad and deep way. Information is combined with first conducting monitoring, then followed by question and answer from various interviewees screened to guide the information obtained also by reviewing bibliography and other sources. The information obtained from direct observation in the field, which is the object of this research is the company and the informants are consumers and citizens. The results of the research show that an important step in implementing change management in improving the organization can be carried out in several stages, namely changes at the individual level, changes at the group level, and changes at the organizational level.